2021
DOI: 10.18178/ijesd.2021.12.2.1318
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Limestone and Anthracite Coal as Filter Media in Treating Pollutants from Groundwater

Abstract: The performance of limestone and anthracite coal were evaluated for the removal of pollutants from groundwater. The physical and chemical properties of two filter materials were characterised through X-Ray diffraction (XRD), X-Ray fluorescence (XRF), field emission scanning electron microscopy (FESEM) and Fourier transform infrared spectroscopy (FTIR). XRD analysis showed that the main peaks of calcite (CaCO3) are the predominant phase of limestone, whereas quartz and graphite are the crystalline phase of anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The difference was thought to be due to the surface roughness of the samples where limestone had a rough surface compared to the smooth surface of calcite [44]. In addition, the surface of limestone has hydrophilic/polar functional groups (hydroxyl (O-H) groups and carbonyl (C=O) groups), which enable easier intake of water [45]. Although the wetting behavior favors limestone, the composites containing limestone fillers in the current study absorbed less water than those containing eggshell fillers.…”
Section: Weight Lossmentioning
confidence: 99%
“…The difference was thought to be due to the surface roughness of the samples where limestone had a rough surface compared to the smooth surface of calcite [44]. In addition, the surface of limestone has hydrophilic/polar functional groups (hydroxyl (O-H) groups and carbonyl (C=O) groups), which enable easier intake of water [45]. Although the wetting behavior favors limestone, the composites containing limestone fillers in the current study absorbed less water than those containing eggshell fillers.…”
Section: Weight Lossmentioning
confidence: 99%
“…On the other hand, Jayabalan et al (2020) reported that AC achieved removal efficiencies greater than 40% for BOD and COD, highlighting its effectiveness in adsorbing and reducing organic matter and pollutants [33]. Meanwhile, BS exhibited 38% to 67% removal of heavy metals from synthetic stormwater [34], whereas AT demonstrated the capability to adsorb organic pollutants due to its hydrophobic characteristics [35]. Overall, this analysis identified the unique contributions, potential advantages, and applications of the filter media evaluated in this study.…”
Section: Performance Evaluation Of Filter Mediamentioning
confidence: 99%
“…The objective of this paper was to find out the levels of decontamination of metals that have been achieved as the contaminated or raw groundwater have gone through successive purification steps, beginning with the air bubbling process, followed by anthracite filtration, and finally by activated charcoal filtration. Air Sparging Procedure is considered as a fast, clean and economical technique [8][9][10]. Dvorak and Skipton [11] reported that Activated carbon (AC) filtration can reduce certain organic compounds and chlorine in drinking water as lead and dissolved radon and suggested that an AC filtration system should be selected based on water analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Dvorak and Skipton [11] reported that Activated carbon (AC) filtration can reduce certain organic compounds and chlorine in drinking water as lead and dissolved radon and suggested that an AC filtration system should be selected based on water analysis. Anthracite is suitable for the adsorption of natural organic matter, because of functional groups present on its surface [9].…”
Section: Introductionmentioning
confidence: 99%